A study on maintenance mosque / Nur Ashikin Jusoh @ Yusof - Jusoh @ Yusof, Nur Ashikin (Faculty of Architecture, Planning and Surveying, 2010)
Recently, we hear about defect at the building even the new building. It can become serious if no action to be taken at this problem. So maintenance for the building very important to make the building long life. To manage the proper maintenance they must have proper organization for the maintenance team to carry out all the maintenance work and to manage for maintenance management. Dou to that, satisfied level of user must be take serious to make sure how far maintenance level doing at the mosque. To measured user satisfaction for the mosque, the research was done at three site wish are located at Putrajaya, Kuala Lumpur, and Shah Alam. Other than that, to determined comfort level at the mosque how the user fill when being in the mosque. From that a maintenance management system is needed to plan, managed and also provide all the building needs to make sure no constrain in manage maintenance work.The finding were that most of the mosque have same level of satisfaction in many aspect and also level of comfort. This is because the maintenance work at the mosque well done and follow their specification and schedule work for maintenance. Also supervise from the expertise persons to make sure they do the right work and on time.